2015
DOI: 10.1364/oe.23.006754
|View full text |Cite
|
Sign up to set email alerts
|

Multi-kW peak power acousto-optically tunable thulium-doped fiber laser system

Abstract: We demonstrate a core-pumped Q-switched thulium-doped fiber laser system with fast tunability capability over 100 nm without any movable part. With up to 7 kW peak power in a diffraction-limited beam, this source is well adapted for pumping a frequency agile mid-IR parametric oscillator or amplifier based on Quasi-Phase-Match single-period crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…However, since the obtained pulse energy and duration are already well-suited to pump both the NesCOPO and a parametric OP-GaAs amplifier, future work will mainly focus on the increase of the overall system efficiency and long-term stability while maintaining a similar working point. The 20 nm tuning range we demonstrated is smaller than what has already been demonstrated with thulium lasers [5][6][7][10][11][12]. In our case, the tuning range is restricted by the current technical limitation of the fabrication process of the TC-VBG.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…However, since the obtained pulse energy and duration are already well-suited to pump both the NesCOPO and a parametric OP-GaAs amplifier, future work will mainly focus on the increase of the overall system efficiency and long-term stability while maintaining a similar working point. The 20 nm tuning range we demonstrated is smaller than what has already been demonstrated with thulium lasers [5][6][7][10][11][12]. In our case, the tuning range is restricted by the current technical limitation of the fabrication process of the TC-VBG.…”
Section: Discussioncontrasting
confidence: 60%
“…In this work we obtained up to 270 µJ pulses with 50 ns pulse duration, providing 5.4 kW peak power on a single longitudinal mode. Most of the reported systems [9][10][11][12][13] present peak powers that also stand in the 1 to 10 kW range but are multi-longitudinal-mode. Reference [7,8,14,15] present much higher peak powers ranging from 20 to 160 kW, but, either they are multi-longitudinal-mode, or they use a much more complex laser design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the tunability range of the NesCOPO can readily be done by adding more QPM tracks in the crystal. The NesCOPO tunability could also be increased or made faster by tuning the pump wavelength directly, which is made possible thanks to the latest 2 μm source developments [68]. In an optical parametric amplifier based on QPM crystals, the tunability can be increased in the same way as in an optical parametric oscillator.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Gutty et al [11] demonstrated a core-pumped Q-switched thulium-doped fiber laser system with fast tuning capability over 100 nm without any movable part. With up to 7 kW peak power in a diffraction-limited beam, this source is well adapted for pumping a frequency agile mid-IR parametric oscillator or amplifier based on quasi-phase-matched single-period crystals.…”
Section: Infrared Lasersmentioning
confidence: 99%